1D NON-LINEAR INVERSION MODELING FOR 3D TDEM SYNTHETIC DATA OF CARBON DIOXIDE (CO2) INJECTION MONITORING SIMULATION - BAGUS SUANANDA YOGI , IDA
Monitoring physical parameter (resistivity) change of reservoir in a geological formation is an important stage to make sure the injected CO2 gas entering the reservoir. In this study CO2 injection will be monitored by time domain electromagnetic (TDEM) method which is started using simulation or modeling. A 3D modeling is important in understanding in a complex geological structure. In recent decades the developments of TDEM 3D modeling program are increasing. However, a 1D inversion has been still used for the inverse modeling. In this study we have performed a 1D non-linear inversion modeling for the synthetic data of 3D model. From this results, we have obtained generally the capability of 3D forward modeling and 1D non-linier inversion algorithm. From this research, we have indicated that TDEM signal is determined by resistivity model, length and current of the transmitter, and the receiver offset. The sensitivity value of the reservoir change was 0.15 - 0.52 (normalization by scaling 0 - 1). In the other hand, 1D inversion result for 3D synthetic data had RMS-error 0.1 % - 0.25 %. 3D anticline structure centerwas changed 100 m upward and 600 m horizontally. However, generally the inversion model could recover the 3D structure feature of of synthetic model. For monitoring purpose, a time lapse model simulating after CO2 injection has shown some differences in TDEM signal curve of 4% difference. Furthermore, the differences have been also indicated in apparent resistivity curve and 1D inversion result section has recovered a 3D structure of model. From this 3D TDEM modeling study, it can be concluded that TDEM method has a capability to monitor CO2 injection process to the reservoir.